KEMAMPUAN BERPIKIR KREATIF MATEMATIS DALAM MENYELESAIKAN SOAL OPEN ENDED PADA MATERI PLDV DI SMP - Theodorus Dominikus; Yulis Jamiah; Ahmad Yani T (Universitas Tanjungpura, 2021)
AbstractThe purpose of this research in general is to determine the ability of mathematical creative thinking in solving epen ended questions on the linear equations material of two variables of class VIII A in SMP Negeri 4 Sungai Ambawang. The research method is descriptive method in form in case study research. The subjects in this research werw 34 students of class VIII A of SMP Negeri 4 Sungai Ambawang and the focus of the research was the ability to think mathematical creatively in solving open ended questions of two-variable linear equations. The result of data analysis showed that students’ mathematical creative thingking ability in the fluency aspect reached 78%, in the flexibelity aspect in reached 58%, and in the novelty aspect it reached 25%.Keywords : Ability to think mathematic creatively, Open ended, Twovariables linear equation